The Unfinished Art of Theater : Avant-Garde Intellectuals in Mexico and Brazil - Townsend, Sarah J. (Book collections on Project MUSE., 2018)
The avant-garde posits the possibility of total rupture with the past. This book pulls back on this futuristic impulse by showing how theater became a key site for artists on the edge of capitalism to reconfigure the role of the aesthetic between 1917 and 1934. The book argues that this "unfinished art"-because of its weakness as a representative institution in Mexico and Brazil, where the bourgeois stage had not yet coalesced-was at the forefront of struggles to redefine the relationship between art and social change. Drawing on archival research, Townsend reveals the importance of avant-garde projects that belie the rhetoric of rupture and immediacy: ethnographic operas, populist puppet plays, children's radio programs, a philosophical drama about the birth of a new race, and an antifascist spectacle written for a theater shut down by the police. The book argues that avant-garde art is tied to the experience of dependency, delay, and the uneven development of capitalism.